Reply to Correspondence on "Carbon‐Centered Radical Addition to O=C of Amides or Esters as a Route to C−O Bond Formations". Issue 32 (24th May 2019) - Liu, Chao; Lei, Aiwen
Abstract : A further understanding on carbon‐centered radical addition to O=C to form C−O bonds is given. Several literature reports were illustrated to show the possibility of carbon‐centered radical addition to O=C to form C−O bond. Generally, the ring‐forming effect and a proper driving force to consume the formed cyclic carbon radical are required to achieve such a process.